Gender-Dependent Associations of Anxiety and Depression Symptoms With Eating Disorder Psychopathology in a Representative Population Sample - Ernst, Mareike; Werner, Antonia M.; Tibubos, Ana N.; Beutel, Manfred E.; de Zwaan, Martina; Brähler, Elmar (Frontiers in Psychiatry, 2021)
Background: Evidence shows that anxiety and depression disorders play an important role in eating disorder behavior. However, given the epidemiology of eating disorders, there is a need to investigate potentially gender-specific connections. Method: This study tested the associations of anxiety and depression symptoms with eating disorder symptoms and behaviors and explored whether they differed between men and women. Within a population-representative survey (N = 2,510; ages 14-94), participants completed measures of depression symptoms (PHQ-2), anxiety symptoms (GAD-2), and eating disorder symptoms (EDE Q-8). We conducted linear regression analyses of the EDE Q-8 sum score and General Linear Models on the three behaviors overeating, binge eating, and compensatory behaviors (self-induced vomiting/use of laxatives/excessive exercising). Results: Depression and anxiety symptoms were related to more eating disorder symptoms in men and women (irrespective of BMI, age, and income). The association of depression and eating disorder symptoms was slightly stronger in women. Overeating was more common in men and in depressed individuals, whereas compensatory behaviors were more common among anxious individuals, especially anxious women. Conclusion: The study extends previous research by using gender-specific methods in a representative sample. It indicates similarities and differences between men and women regarding disordered eating on a population level.